Futuristic vision and technology for innovative libraries - SIngh, Rajesh; Sukula, Shiva Kanaujia (ON, Canada Society Publishing, 2024)
"Digital in every sense, the libraries are transforming with significant leaps in technology taking place every day. Whereas the patrons are expecting libraries to provide a seamless, accessible experience, the libraries are finding new ways for sustainability, change management, and flexibilities by applying library standards. The edited book has been focusing on various management models and frameworks in library services. The theme has been introduced with a view to identify different models, standards, and tools which can be used to bring change in the ICT environment. It is expected to generate a large number of views from across the world which has far-reaching impact on developing the best out of all. The books especially focuses on faculty-student-library collaboration in all spheres of activities in the academic libraries. It underscores the collaboration of all stakeholders for holistic development of the academic library system. The content in the book also focuses on the institutional involvement in providing better manpower, better financial outlay based on the emerging practices. There has been much emphasis on the emerging management models for academic libraries; manpower structure in ICT environment; evolving ways and means for better relationship for working with faculty; user-centric services; reference and outreach; changes in emerging user characteristics, behaviors, and expectations; analyzing users' expectations in the emerging digital environment; information literacy and competency programs, e-tutorials along with best practices on modern library services." --Back cover.
Keywords: Libraries -- Automation; Information technology